2017
DOI: 10.1177/1461444817702397
|View full text |Cite
|
Sign up to set email alerts
|

Platform privacies: Governance, collaboration, and the different meanings of “privacy” in iOS and Android development

Abstract: Mobile application design can have a tremendous impact on consumer privacy. But how do mobile developers learn what constitutes privacy? We analyze discussions about privacy on two major developer forums: one for iOS and one for Android. We find that the different platforms produce markedly different definitions of privacy. For iOS developers, Apple is a gatekeeper, controlling market access. The meaning of “privacy” shifts as developers try to interpret Apple’s policy guidance. For Android developers, Google … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 20 publications
(15 reference statements)
1
45
0
1
Order By: Relevance
“…This code eventually encompassed decision-making or analytical processes that implicitly or explicitly required expert knowledge, and birthed several subcodes used to distinguish sub-categories of expertise (e.g., 'technical' or 'legal'). Informed by prior discourse analyses of digital researchers [58] and technologists [59], the other authors collated and reviewed a set of shared themes and noted divergences, with reference to the sample and the prior stage's codes. Some divergences prompted a return to first-order coding, to ensure similar phenomena were coded similarly.…”
Section: Frame Analysismentioning
confidence: 99%
“…This code eventually encompassed decision-making or analytical processes that implicitly or explicitly required expert knowledge, and birthed several subcodes used to distinguish sub-categories of expertise (e.g., 'technical' or 'legal'). Informed by prior discourse analyses of digital researchers [58] and technologists [59], the other authors collated and reviewed a set of shared themes and noted divergences, with reference to the sample and the prior stage's codes. Some divergences prompted a return to first-order coding, to ensure similar phenomena were coded similarly.…”
Section: Frame Analysismentioning
confidence: 99%
“…I think it's essential" (Fleischmann, Wallace, and Grimes 2010, 3). Similarly, Greene and Shilton (2018) found that an "ethic of care" for users is common among app developers. They concluded that developer forums such as the iPhoneDevSDK forum and the Android XDA forums act as quasi-regulators, setting privacy expectations for applications to be published on their platform stores and thereby guiding app developers' privacy efforts.…”
mentioning
confidence: 98%
“…Recently, the United States' Federal Trade Commission (FTC) has sought to enhance mobile data protection through 'privacy by design.' Here developers are being encouraged to proactively implement best-practice privacy features to protect sensitive data (Greene and Shilton 2017). They effectively become 'ethical agents', expected to take responsibility for the privacy implications of their technical design decisions (Greene and Shilton 2017).…”
Section: Toward Cooperative Responsibilitymentioning
confidence: 99%